HUBUNGAN SPRINT DAN KEMAMPUAN AGILITY PADA PEMAIN BASKET MADRASAH ALIYAH NEGERI 4 JAKARTA - Marselly Raytami (2022)
One of the most popular sports activities in Indonesia is basketball. Starting from elementary schools, junior high schools, senior high schools to universities, they have special extracurricular ball sports at Madrasah Aliyah Negeri 4 Jakarta or abbreviated as MAN 4 Jakarta. In basketball, there are complex movement patterns, including running speed and agility. The main purpose of this study was to examine the relationship between sprinting ability and agility performance in basketball players at Madrasah Aliyah Negeri 4 Jakarta. The research design used by the author is a cross sectional study. The sample consisted of 30 (n = 30) beginner basketball players (mean: age = 15 - 17 years; height = 150 - 180 cm; weight = 50 - 80 kg) participated in this study. The 30 meter sprint test is a parameter to measure sprint ability and the Agility T-Test is to assess agility performance. Based on the results of this study, the sprint performance was dominated by the very good category with a percentage of 53.3%. Furthermore, the agility ability is dominated by the good category with a percentage of 36.7%. The data is then processed using the Pearson product moment test technique which produces results between sprint and agility having a significance test possibility of p = 0.152, so it can be said that there is no keyword between sprint and agility and the results of the Pearson sprint correlation r = 0.268 then this value has a low degree of correlation. between sprinting and agility.